House of Innovation - Social Innovation Scholarship - Stockholm School of Economics (Stockholm School of Economics)
The purpose of the social innovation scholarship is to enable SSE students to pursue opportunities within the realm of social entrepreneurship and social innovation. It represents an opportunity for SSE students to spend the summer working for and supporting a social entrepreneur or NGO somewhere in the world. It is a chance to leverage their business skills to create real change.
Keywords: Bourses de stages; Europe; Université

House of Innovation - Social Innovation Scholarship - Stockholm School of Economics (Stockholm School of Economics, 2022)
The purpose of the social innovation scholarship is to enable SSE students to pursue opportunities within the realm of social entrepreneurship and social innovation. It represents an opportunity for SSE students to spend the summer working for and supporting a social entrepreneur or NGO somewhere in the world. It is a chance to leverage their business skills to create real change.
Keywords: Bourses de stages; Europe; Université